2005
DOI: 10.1111/j.1440-1800.2005.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and professional identity in psychiatric nursing practice in Alberta, Canada, 1930–75

Abstract: This paper examines gender-specific transformations of nursing practice in institutional mental health-care in Alberta, Canada, based on archival records on two psychiatric hospitals, Alberta Hospital Ponoka and Alberta Hospital Edmonton, and on oral histories with psychiatric mental health nurses in Alberta. The paper explores class and gender as interrelated influences shaping the work and professional identity of psychiatric mental health nurses from the 1930s until the mid-1970s. Training schools for nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
(35 reference statements)
1
28
0
1
Order By: Relevance
“…Boschma et al [9] examined nurses' stories that further the understanding of the development of PMHN in Alberta. RN status was recognized as being desirable for PMHN and could be achieved by mental health nurses by taking an extra 18 months of training in a general hospital after completing 2 years in a psychiatric hospital.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Boschma et al [9] examined nurses' stories that further the understanding of the development of PMHN in Alberta. RN status was recognized as being desirable for PMHN and could be achieved by mental health nurses by taking an extra 18 months of training in a general hospital after completing 2 years in a psychiatric hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, the deinstitutionalization trend that began in the 1960s resulted in many persons with mental illness being released into the community where a serious lack of mental health services prevailed [9]. This led to a significant portion of individuals with mental illness to become imprisoned in jails or detention centers with limited access to mental health care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) To facilitate discussion and modelling of professional values in nursing education and clinical practice, the abstract attributes of professionalism have to reflected in tangible behaviours (Green et al 2009). (16) Few studies discussed teaching professionalism in nursing education (Chiovitti 2015;Ghadirian et al 2014;Castell 2008), (18,19,20) particularly in psychiatry (Boling 2003;Boschma et al 2005). (9,21) This study reported professionalism education to nursing students in an Arabian context.…”
Section: Introduction:-mentioning
confidence: 99%
“…(16) Few studies discussed teaching professionalism in nursing education (Chiovitti 2015;Ghadirian et al 2014;Castell 2008), (18,19,20) particularly in psychiatry (Boling 2003;Boschma et al 2005). (9,21) This study reported professionalism education to nursing students in an Arabian context. As indicated above, professionalism is culture-specific and its attributes in the Arabian context was linked to core values and faith.…”
Section: Introduction:-mentioning
confidence: 99%